Autograft Choice in Young Female Patients: Patella Tendon versus Hamstring - Shakked, Rachel; Weinberg, Maxwell; Capo, Jason; Jazrawi, Laith; Strauss, Eric (The Journal of Knee Surgery, 2017)
With the increasing incidence of anterior cruciate ligament (ACL) reconstruction in women and younger patients, the optimal graft choice in the young female patient has become the subject of much debate. This study aimed to evaluate patient-reported outcomes, objective knee stability, complication rates, and the incidence of failure after ACL reconstruction using bone–patellar tendon–bone (BPTB) autograft compared with hamstring (HS) autograft in young female patients. Female patients who underwent primary ACL reconstruction with BPTB or HS autograft between ages 15 and 25 years were identified. Medical records were reviewed for postoperative complications and subsequent procedures on the operative knee. Patients were evaluated with functional surveys, physical examination including Lachman and pivot-shift tests, and arthrometric testing with a KT-1000 arthrometer. There were 37 patients in the BPTB group and 28 patients in the HS group. For patients who did not undergo revision, significant differences were not found in visual analog score (p = 0.94), Lysholm score (p = 0.81), Kujala score (p = 0.85), or Tegner level (p = 0.81). No difference was detected in the rate of return to a level of activity at or above the same level prior to injury (p = 0.31). Significantly more patients in the BPTB group were graded 1a Lachman and negative pivot shift compared with the HS group (p < 0.001). There was a significant difference in mean side-to-side manual maximum arthrometric testing (p < 0.001). There were significantly fewer subsequent procedures and a lower rate of graft failures in the BPTB group. We detected no difference in subjective functional outcomes following ACL reconstruction. However, a higher failure rate in the HS reconstructions and greater laxity by arthrometric testing may indicate increased objective stability with the use of BPTB autograft in the young female patient population. The level of evidence for this article is (level III, retrospective cohort).
Keywords: ACL reconstruction; female; patella tendon; hamstring tendon; autograft